The management of traumatic and non traumatic dacryostenosis with endoscopy dacryocystorhinostomy - Dolly Irfandy; Al Hafiz; Rimelda Aquinas; Hendriati - (Oto Rhino Laryngologica Indonesiana, 2021)
ABSTRACTBackground: Dacryostenosis is a condition of obstruction or stenosis of the nasolacrimal duct, causing excessive tearing. Endoscopic dacryocystorhinostomy (endo-DCR) is an endoscopic procedure for nasolacrimal duct obstruction management. Purpose: To report and analyze the result of endo-DCR in dacryostenosis cases that caused by traumatic and non-traumatic etiology. Case report: Two cases of nasolacrimal duct obstruction on 26 years old and 63 years old women. Endo-DCR was performed to the patients in join operation with the Ophtalmology Department. On 3 months follow up, there were no epiphora, nor recurrent infection. On anel test the nasolacrimal duct was patent. Clinical question: Is endo-DCR an appropriate procedure for traumatic and non-traumatic dacryostenosis cases? Review method: Literature search was performed with keywords: “dacryostenosis” AND “dacryocystorhinostomy” AND “endoscopy”. Result: The literature search through Cochrane Database, Science Direct, and Springer Link produced 104 published works, and after screening by entering keywords was carried out, resulting in 12 relevant literatures. Selection of the last 5 years produced 2 appropriate journals. Conclusion: Management of traumatic and non-traumatic dacryostenosis with endo-DCR provided excellent result. In these cases, the join operation between Otorhinolaryngologist and Ophthalmologist were very beneficial for the patients.Keywords: dacryostenosis, nasolacrimal duct, endoscopy, dacryocystorhinostomyABSTRAKLatar belakang: Dakriostenosis adalah kondisi obstruksi atau stenosis duktus nasolakrimal sehingga keluar air mata yang berlebihan. Dakriosistorinostomi per endoskopi merupakan prosedur endoskopi untuk penatalaksanaan obstruksi duktus nasolakrimalis. Tujuan: Melaporkan dan menganalisis hasil dakriosistorinostomi per endoskopi pada kasus dakriostenosis yang disebabkan oleh trauma maupun non-trauma. Laporan kasus: Dilaporkan 2 kasus obstruksi duktus nasolakrimalis pada wanita usia 26 tahun dan 63 tahun. Pada pasien dilakukan dakriosistorinostomi per endoskopi, operasi bersama dengan Bagian Ilmu Kesehatan Mata. Setelah follow up 3 bulan, tidak ada epifora dan infeksi pada mata. Dengan pemeriksaan tes anel didapati duktus nasolakrimalis paten. Pertanyaan klinis: Apakah tindakan dakriosistorinostomi per endoskopi merupakan tidakan yang tepat untuk kasus obstruksi duktus nasolakrimalis karena trauma maupun non-trauma? Telaah literatur: Pencarian bukti dilakukan melalui Cohchrane, Science Direct, dan Springer Link. Hasil: Didapatkan 104 literatur yang terkait. Setelah dilakukan skrining diperoleh 12 literatur yang relevan. Pemilihan jurnal 5 tahun terakhir dengan memasukkan kata kunci, diperoleh 2 jurnal yang sesuai. Kesimpulan: Penatalaksanaan dakriostenosis karena trauma ataupun non-trauma, dengan dakriosistorinostomi per endoskopi memberikan hasil yang memuaskan. Pada kedua kasus ini, kerja sama antara dokter spesialis THT-KL dan spesialis Mata memberikan manfaat untuk pasien.Kata kunci: dakriostenosis, duktus nasolakrimalis, endoskopi, dakriosistorinostomi